2022
DOI: 10.1108/bfj-01-2022-0019
|View full text |Cite
|
Sign up to set email alerts
|

Household food wastage in Montenegro: exploring consumer food behaviour and attitude under COVID-19 pandemic circumstances

Abstract: PurposeThe purpose of the research was to determine food consumer behaviour and attitudes towards food consumption and household food waste in Montenegro. Since the period of conducting the research coincided with the expansion of the coronavirus disease 2019 (COVID-19) pandemic in Montenegro (10–14 weeks since its outbreak), the results of this research could indicate the emerging pandemic circumstances.Design/methodology/approachA total of 529 consumers were surveyed online, and 514 questionnaires met the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 70 publications
2
8
1
1
Order By: Relevance
“…In terms of food waste, in a survey carried out during the most restrictive phase of the containment measures against COVID-19 in Italy, the awareness of food surplus and waste was reported by nearly 80% of participants who claimed to have consumed all the food they cooked and reported to have had the capacity to store surplus and consume the leftovers ( 44 ). The consumers’ awareness toward food waste during the pandemic period was confirmed by other European studies ( 45 47 ). According to Principato et al ( 48 ), in Italy, the unexpected positive effect of the lockdown caused by the pandemic was that most consumers threw away less food in comparison to the pre-pandemic situation with a better implementation of food management practices (shopping list, meal planning, etc.).…”
Section: Discussionsupporting
confidence: 70%
“…In terms of food waste, in a survey carried out during the most restrictive phase of the containment measures against COVID-19 in Italy, the awareness of food surplus and waste was reported by nearly 80% of participants who claimed to have consumed all the food they cooked and reported to have had the capacity to store surplus and consume the leftovers ( 44 ). The consumers’ awareness toward food waste during the pandemic period was confirmed by other European studies ( 45 47 ). According to Principato et al ( 48 ), in Italy, the unexpected positive effect of the lockdown caused by the pandemic was that most consumers threw away less food in comparison to the pre-pandemic situation with a better implementation of food management practices (shopping list, meal planning, etc.).…”
Section: Discussionsupporting
confidence: 70%
“…Several previous studies showed that the first waves of the COVID-19 pandemic affected out-of-home food-related activities and practices such as food purchasing and procurement practices in several countries such as Bosnia and Herzegovina (Ben Hassen et al ., 2021c), Czech Republic (Eger et al ., 2021), Iran (Allahyari et al ., 2022), Italy (Principato et al ., 2020), Montenegro (Vasko et al ., 2022), North Macedonia (Bogevska et al ., 2021), Russia (Ben Hassen et al. , 2021a), Serbia (Ben Hassen et al ., 2021b; Berjan et al ., 2022; Marinković and Lazarević, 2021), the United States of America (Rodgers et al ., 2021) and Tunisia (Jribi et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…4. Temperature-Controlled Food Concerns (Navickas et al, 2015;Vasko et al, 2022;Park, 2023;Seghezzi et al, 2023): Dedicated to understanding perceptions and concerns related to temperature-controlled foods purchased online, this section explored purchase frequencies, types of foods bought, safety and nutritional concerns, trust in grocery store temperature control mechanisms, and confidence in the quality of these foods when bought online.…”
Section: Methodology: Assessing Digital Transformation In E-grocery C...mentioning
confidence: 99%